Study of iatrogenic bladder injury in vaginal hysterectomy: our experience - Singh, Pooja S.; Doshi, Haresh U. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was carried out to calculate the incidence of bladder injury detected during benign gynecologic vaginal hysterectomy. This investigation examined the clinical features of urologic complications during gynecologic surgery and outcome of their management. Methods: It was a retrospective study done at Department of Gynecology, GCS medical college, Ahmedabad from year 2012-2016. All patients undergoing vaginal hysterectomy for benign diseases were included in the study. This study assessed the causative disease and surgical approach type, and treatment method of the bladder injury. Results: Of these 237 patients who underwent vaginal hysterectomies, 3 (1.26%) had bladder perforation. All the 3 cases of bladder injury underwent primary suturing during surgery without complications. Conclusions: Bladder injury was the most common urological injury during obstetric and gynecologic surgery. Early diagnosis and urologic intervention is important for better outcomes.